Prevalence of speech problems among school children of Mysore city - Manohar PD; Jayaram M (Journal of All India Institute of Speech and Hearing, 1973)
Studies regarding the incidence of speech problems in general population as well as school children have not been reported so far in country on a large sample, though there are studies regarding the incidence of hearing problems. In 1968, Dr Hegarty of New Delhi in a pilot study of the seventh standard schoolgoing children found that 22/322 children were speech defectives and thus concluded that 7 per cent of the school-going children are speech defectives. In1969, Mr E. P. Balakrishnan at Mysore in a study of 1000 school going children found that 15 per cent of them had speech disorders. The problemwise percentagehe gives are 6.6 per cent of them had misarticulations, 3.8 per cent of them had dysphonias, 4.5 per cent of them had stuttering. As our speech and hearingfield is growing rapidly and gaining importance there is every reason for initiating these studies which will serve many practical purposes. Towards this aim asmall beginning is made at our Institute. The institute has a screening programme for detecting the speech and hearing problems for the conservation and rehabilitationamong school children. This report is the analysis of the speech evaluationcarried out from 17 Dec. 1970 to 29 Sept. 1972 in Mysore City to find anestimate of various speech problems in the school children which is a part of thescreening programme of the All India Institute of Speech and Hearing, Mysore.